Representation of National Final Exam in Indonesian News of detik.com - R. Nadia R. P. Dalimunthe (International Conference on Education and Language (ICEL), 2014)
National FinalExam is the questionable policy that the government has taken to improve the quality of national education. It becomes one favorite topic of mass media in Indonesia. Some related studies have proven that mass media are likely to mislead their news due to certain interests. This study aimed to observe how national final exam is represented in Indonesian news. It was a critical media discourse study. The analysis focused on three main levels: textual analysis, discursive practice, and social practice. The data were taken from news articles which were published in Detik.Com, the most visited news website, in 2013.